2016
DOI: 10.1007/978-1-4939-6588-5_20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cardiac Surgery with Recirculating Delivery (MCARD): Procedure and Vector Transfer

Abstract: Despite progress in clinical treatment, cardiovascular diseases are still the leading cause of morbidity and mortality worldwide. Therefore, novel therapeutic approaches are needed, targeting the underlying molecular mechanisms of disease with improved outcomes for patients. Gene therapy is one of the most promising fields for the development of new treatments for the advanced stages of cardiovascular diseases. The establishment of clinically relevant methods of gene transfer remains one of the principal limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Preclinical studies with this endovascular device show that it can directly access target tissues, such as the heart, kidney and pancreas, without the need to seal the puncture site 146 . Re-circulation devices, which allow the agent to pass the area of interest multiple times, can enhance transduction efficiency in large animal models 174 . Selective pressure-regulated retroinfusion (SSR) with blockage of the antegrade flow is another promising approach for safe, efficient delivery of various agents, including cDNA, miRNA inhibitors and gene therapeutic agents 175 .…”
Section: Catheter Deliverymentioning
confidence: 99%
“…Preclinical studies with this endovascular device show that it can directly access target tissues, such as the heart, kidney and pancreas, without the need to seal the puncture site 146 . Re-circulation devices, which allow the agent to pass the area of interest multiple times, can enhance transduction efficiency in large animal models 174 . Selective pressure-regulated retroinfusion (SSR) with blockage of the antegrade flow is another promising approach for safe, efficient delivery of various agents, including cDNA, miRNA inhibitors and gene therapeutic agents 175 .…”
Section: Catheter Deliverymentioning
confidence: 99%
“…Summarizing, it has been demonstrated that complete surgical isolation of the heart in situ , using CPB with high-pressure retrograde coronary sinus infusion with multiple-pass recirculation of vector through the heart results in an increase of several orders of magnitude in cardiac marker gene activities compared with controls, receiving retrograde infusion of adenovirus without CPB and without cardiac isolation [ 16 ]. The principal strength of this technology includes a dramatic (>1000-fold) increase in transduction efficiency, the extension of vector residence time, the ability to manipulate endothelial permeability, the avoidance of an immune response to the vector and the ability to washout the vector post gene delivery limiting collateral organ exposure [ 17 ]. “Closed loop” systems such as MCARD can provide robust gene expression with no detectable extra-cardiac transfer and no detrimental effects on major organ function.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Because of its invasiveness, this method is rarely used; see [14] for a detailed description. For reviews describing delivery methods that are suitable for large animal models and humans, see [15-19]. …”
Section: Introductionmentioning
confidence: 99%